2015
DOI: 10.1007/s12178-015-9293-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of spacers (static and mobile) in infection knee arthroplasty

Abstract: Revision total knee arthroplasty (TKA) is the treatment of choice in patients with periprosthetic joint infection. It may be performed in either a single stage or two stages. In the latter option, between stages, an antibiotic-loaded spacer may be used to maintain a certain amount of joint stability and mobility after the infected implant is removed, adding an intra-articular concentration of antibiotics. There are two types of antibiotic-loaded cement spacers: static and dynamic. Static spacers basically crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
81
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 86 publications
1
81
0
8
Order By: Relevance
“…A review by Mazzucchelli et al reported that articulating spacers may not be used in cases where patients are found to have inadequate soft tissue cover over the knee since it may lead to problems with wound healing (28). Numerous studies have also reported that spacer fractures are a common postoperative complication of using articulating spacers (31)(32).…”
Section: Articulating Spacersmentioning
confidence: 99%
See 4 more Smart Citations
“…A review by Mazzucchelli et al reported that articulating spacers may not be used in cases where patients are found to have inadequate soft tissue cover over the knee since it may lead to problems with wound healing (28). Numerous studies have also reported that spacer fractures are a common postoperative complication of using articulating spacers (31)(32).…”
Section: Articulating Spacersmentioning
confidence: 99%
“…Articulating spacers have been found to result in a greater postoperative ROM with the same rate of infection control (28). These are several factors for this better outcome, though the main one is the preservation of the length and elasticity of extensor mechanisms.…”
Section: Articulating Spacersmentioning
confidence: 99%
See 3 more Smart Citations